1994
DOI: 10.1159/000292435
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships of Serum Paraoxonase, Serum Lipids and Apolipoproteins in Normal Pregnancy

Abstract: Serum paraoxonase (EC 3.1.1.2) may be implicated in the lipid metabolism. In order to substantiate this view we conducted a longitudinal study of interrelationships of serum paraoxonase, lipids and apolipoproteins during pregnancy. Fasting serum levels of paraoxonase, serum lipids (total, HDL and LDL cholesterols, triglycerides) and apolipoproteins (AI, All and B) were estimated in 91 pregnant women at 28 and 32 weeks of gestation and 6 weeks after delivery, and 40 nonpregnant women. Serum paraoxonase, total H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 8 publications
3
10
2
Order By: Relevance
“…mice are more susceptible to organophosphate toxicity (Shih et al 1998). A previous study (Roy et al 1994) reported a negative correlation between PON1 activity and birth weight. We found no significant relationship between PON1 activity or PON1 genes and birth weight.…”
Section: Discussionmentioning
confidence: 95%
“…mice are more susceptible to organophosphate toxicity (Shih et al 1998). A previous study (Roy et al 1994) reported a negative correlation between PON1 activity and birth weight. We found no significant relationship between PON1 activity or PON1 genes and birth weight.…”
Section: Discussionmentioning
confidence: 95%
“…Several nongenetic factors seem to contribute to modulating serum PON levels: diet [23], acute phase reactants [24], pregnancy [25], hormonal factors [26], cigarette smoking [27] and statin therapy [28]. PON can also act as a lactonase on statins, producing metabolites with antioxidant properties.…”
Section: Discussionmentioning
confidence: 99%
“…High-density lipoprotein (HDL) cholesterol is also increased. 81 The triglyceride, fatty acid and LDL cholesterol changes are accentuated but HDL reduced in PE. 68,82 Changes in fatty acids and triglycerides antedate clinically evident PE.…”
Section: Lipids In Pre-eclampsiamentioning
confidence: 99%